Sabang Submarine Volcano Aceh, Indonesia: Review of Some Trace and Rare Earth Elements Abundances Produced by Seafloor Fumarole Activities - Hananto kurnio; Ildrem Syafri; Adjat Sudradjat; Mega Fatimah Rosana (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.3.173-182Geochemical analyses of selected coastal and seafloor samples from Sabang Area revealed abundances of trace and rare earth elements. The selected samples of element abundances were mostly taken from seafloor in the vicinities of active fumaroles either by grab sampler operated from survey boat above fumarole point or by diver directly took the samples on the seafloor especially at Serui - Sabang Bay. Results show that samples closed to seafloor fumaroles demonstrate plenty of trace and rare earth elements. The trace and rare earth elements mean values (n=10) are: Nb (4.33 ppm), La (16.52 ppm), Ce (38.82 ppm), Nd (19.15 ppm), Ce (38.82 ppm), Pr (4.907 ppm), Nd (19.15 ppm), Sm (4.04 ppm), Gd (3.95 ppm), Dy (3.38 ppm), Th (6.432 ppm), and U (4.335 ppm). Negatively, statistical correlations between Fe, Zn, and Ni as the main sulphide elements with sulphur is interpreted that sulphide minerals do not form in the Sabang Sea. Sea water influence in the mineralization process was shown by the good correlations between Fe, Zn, Pb, Ni, and Ba.